ДИНАМІКА НЕСПІВМІРНОЇ НАДСТРУКТУРИ В КРИСТАЛАХ ІЗ СИМЕТРІЄЮ ТЕРМОДИНАМІЧНОГО ПОТЕНЦІАЛУ n=4 - Serhiy Sveleba; Ivan Katerynchuk; Ivan Kuno; Yaroslav Shmygelsky; Serhiy Velgosh; Yu. Bukhnii (Електроніка та інформаційні технології, 2024)
In the Python software environment, Fourier spectra, Lyapunov exponents, maps of dynamic modes, wave vector of an incommensurate superstructure for a system of differential equations of the second order, where the appearance of an incommensurable superstructure is due to the Lifshitz invariant, under the condition n = 4 was performed.